Wyniki analiz spektrometrycznych dwóch dzbanów fenickich z kolekcji gołuchowskiej - Krueger, Michał; Głuszek, Inga (Folia Praehistorica Posnaniensia, 2018)
This paper presents results of the spectrometric analyses of two Phoenician jugs from the Gołuchów collection. A non-invasive portable X-ray fluorescence spectrometer (pXRF) has been used to determine the chemical composition of the jugs. The aim of this work was to add new results to a database of spectrometric data of Phoenician pottery from central and western Mediterranean. Good agreement obtained between the chemical results of the two jugs suggest that they could have been made from the same clay.